Conditional Cash Transfer : Programs an Effective Tool for Reaching the Poorest and Most Vulnerable - Vermehren, Andrea (World Bank, Washington, DC, 2012)
Conditional cash transfer (CCT) programs give families cash to pay for basic health and school expenses (if children attend school and regularly visit health clinics). CCTs have two main objectives: to increase income and alleviate poverty in the short term, and to break the inter-generational cycle of poverty by increasing human capital. Various situations have led to their creation in different countries. The World Bank (WB) supports CCTs in Latin America, Eastern Europe, the Middle-East and Far East. In 2002, the Bank's Latin American and Caribbean Region and the Mexican government sponsored the first regional workshop on experiences with CCTs.. This article summarizes the lessons of experience in designing and operating CCTs shared by officials, donors and academics at the workshop.